(untitled) (Revista Venezolana de Salud Pública, 2020)
This essay is based on the development of a body of argumentation of reality in agrifood and public health that underpins the agrifood model of hegemonic domination, thus justifying the importance of the transformation of productive economic development, its relations with the Public health, from the complexity of reality, living conditions and social reproduction, that is why the advancement of a grounded theory that guides agri-food development in the sphere of production, distribution, consumption, access to feeding opportunities in Venezuela and their relationship with the world in the context of environmental preservation and life from the paradigm of complexity, using the hermeneutical method with the use of dialectics as a strategy in discursive argumentation.